José Luis Malo de Molina y Pablo Martín-Aceña (Eds.): Un siglo de historia del sistema financiero español, Madrid, Alianza Editorial, 2011, 456 págs. - Novo Peteiro, José Antonio (Investigaciones de Historia Económica, 2019)
Sin resumen